How can Public Professional Services be Restored in a Weak State? Options for Animal Health in Congo's South Kivu. (27th September 2017) - Leonard, David K.; Mushi, Mugumo F.; Robinson, Timothy P.
Summary: How does one deal with a shortcoming in a public service when even a state "pocket of effectiveness" is unlikely to fill it directly? In the Belgian colonial era, South Kivu Province in eastern Democratic Republic of Congo had a vibrant animal production system, which then was shattered by successive wars. The regeneration of Kivu's livestock industry is greatly constrained by the unreliability of the province's state and private animal health services, which have become commercialized and are unable to overcome the asymmetric information problem inherent to the professions and provide the trustworthy effectiveness farmers need to use them effectively. The Congolese state is unlikely to be able to fill this gap itself. Nonetheless, it can be an architect of solutions to the problem. We were able to identify in the local institutional repertoire at least four possible ways policy‐makers could use non‐governmental organizations to provide missing trustworthiness to the market. This conclusion is hopeful for places with development potential that have weak states and imperfect markets. © 2017 International Livestock Research Institute. Public Administration and Development published by John Wiley & Sons, Ltd.